Efficient nonresonant dipole force on molecules by a tightly focused laser - Sun, Xing Nan; Shin, So Eun; Zhao, Bum Suk; Chung, Doo Soo (Frontiers in Physics, 2014)
When a molecule is placed in a nonresonant laser field, the Stark interactions between the laser field and the induced molecular dipole result in a mechanical force on the molecule. This nonresonant dipole force is proportional to the intensity gradient of the laser, thus requiring a strong and focused pulsed laser for a sizable impact on the molecule. 36.4 mJ pulses of a 1064 nm Nd:YAG laser focused with a 17.5 cm focal length convex lens produced a 6.4 m/s change in the transverse velocity of a CS2 molecular beam. Using spherical mirrors with shorter focal lengths such as 10.0, 7.5, and 5.0 cm, dipole forces of similar magnitude were obtained with laser pulses of much lower energies. In particular the 5.0-cm focal length spherical mirror provided an 11.3 m/s change in the transverse velocity using 3.6 mJ laser pulses. This corresponds to 18-fold increase in the deflection efficiency, the ratio between the maximum velocity change and the pulse energy. From the improved efficiency, the nonresonant dipole force can be exerted with ease.